Analisis Perumusan dan Pilihan Strategi Bisnis pada Butik Saffana Surabaya - Muchammad Saifuddin; Siti Hasnaa Madinah (IQTISHODUNA, 2022)
Saffana Boutique is a business in the field of exclusive ready-to-wear and custom clothing by designer Saffana who is also the owner of the boutique. The purpose of this research is to explore the right strategy for SAFFANA Surabaya Boutique to face business competition. This qualitative research uses a descriptive case study approach, with research objects being internal and external factors of SAFFANA boutique Surabaya. The data collection technique used was through participatory observation, both structured and in-depth interviews, and documentation. The data that has been obtained were analyzed using a strategy formulation framework model through matrices as an analytical tool arranged sequentially with three decision-making stages, namely the input stage (IFE-EFE Matrix), the basic stage (IE-SWOT-GS Matrix), and the decision stage (QSPM). The final result of this study concludes that the appropriate main alternative strategy for SAFFANA boutiques is market development followed by a horizontal integration strategy and development product strategy.